FTSE WGBI, us balance sheet policy and foreign holdings of Malaysia government securities - Zaidey Evon; Lee, Hock Ann; Ho, Yew Joe (European Publisher, 2020)
On 15th April 2019, it was announced that FTSE Russell has placed Malaysia on the watch list in reviewing Malaysia position in the FTSE World Government Bond Index (WGBI). This announcement contributes to the current debates on the potential effects pertaining to Malaysia’s future position in the WGBI especially its effect on foreign holdings of Malaysia Government Securities (MGS) as the recent data have shown Malaysia weight in the WGBI is equivalent to MYR 16.2 billion or 11% of foreign holdings of MGS. Hence, this research primarily aims to address these ongoing debates by investigating the direct effect of WGBI towards the level of foreign holdings of MGS in Malaysia. Further, this research will also investigate the effect of domestic or pull factors and the US balance sheet policy on the level of foreign holdings of MGS. This research employs monthly data from January 2008 until April 2018 and Auto regressive Distributed Lag (ARDL) method. The empirical results reveal that the inclusion of Malaysia in the WGBI has no significant effect towards the level of foreign holdings of MGS. Consistent with the literature, this research finds that US balance sheet policy is more significant in influencing the level of foreign holdings of MGS. Further, the positive and significant association between US balance sheet policy and foreign holdings of MGS indicates the need for the government of Malaysia to craft relevant policies to mitigate against the risks in the event of US balance sheet policy reversal.